Results of Onlay Preputial Flap Urethroplasty for the Single-Stage Repair of Mid- and Proximal Hypospadias - Ricardo González; Anja Lingnau; Barbara Magda Ludwikowski (Frontiers Media S.A., 2018)
AimsTo report current results of preputial flap onlay urethroplasty using the principle of the total preputial flap (TPF) for the one-stage repair of mid- and proximal hypospadias.MethodsThis study was a retrospective chart review of patients in a prospectively kept database of all hypospadias operations performed at two institutions from January 1 2011 to August 2017. Inclusion criteria: all patients who underwent hypospadias repair using a preputial only flap urethroplasty based on the principle of the TPF. Demographic data, duration of follow-up, complications, and reoperations were recorded. A successful result was considered to be a straight penis, a glanular meatus, and absence of voiding symptoms. Whenever possible an uroflow was obtained during the follow-up visits.ResultsForty-nine children met the inclusion criteria. All patients had marked penile curvature. Three patients had chromosomal abnormalities. The mean age at the time of surgery was 22 months (11-110) and the mean duration of follow-up 23.4 months (1-79). In 48 cases, the urethral plate could be preserved without dividing it. The penile curvature was corrected with chordectomy alone in 10 patients, 38 required a dorsal plication of the tunica albuginea, and 1 required an additional ventral dermal graft. In 38 patients (77.5%), the initial operation was successful, and no further operations were needed. There were eight urethrocutaneous fistulas, three dehiscences of the glans approximation. One patient suffered a wound infection and partial loss of the flap.ConclusionOne-stage repair of mid- and proximal hypospadias preserving the urethral plate and using a TPF for the urethroplasty and coverage of the ventral penis is successful in 77.5% of cases. Complications in the remaining patients were easily managed or did not require treatment. Compared to a planned two-stage approach, the technique described in this report resulted in significantly fewer procedures till complete resolution of the problem.